Pengembangan Program Studi Perbankan Syariah Berbasis Integrasi Peran Bank Syariah Bagi Sektor Riil UMKM - Tri Mulato; Sudirman Sudirman; Kamaruddin Kamaruddin; Iryani Iryani (Jurnal Ilmiah Ekonomi Islam, 2021)
Sharia banking are interested in getting involved channeling financing to the real sector of SMEs, including Bank BNI Syariah Makassar and Bank Panin Dubai Syariah Makassar. The purpose of this study is to determine the development of SMEs financing provided by sharia banking. Then to find out the role of sharia banking for the distribution financing for SMEs in the city of Makassar. As well as to find out the form of integration of the development of the department of sharia banking UIN Alauddin Makassar, through the distribution of financing for SMEs in sharia banking institution. This type of research is a field research, by taking data directly. The nature of the research is qualitative. The data source uses primary data and secondary data related to the research theme. The data analysis technique used in this research is qualitative descriptive, which describes the objects in the study. The results of this study indicate the development of the distribution of financing in sharia banking reaching 15.93 percent. Then Bank BNI Syariah and Bank Panin Dubai Syariah Makassar channeled financing to SMEs sector, reaching 20 percent. The form of integration in the development of departement sharia banking is by presenting courses on object management of financing sharia banking and courses on SMEs business.